INDONESIAN EFFORTS TO CONSERVE GEMBRONG GOATS - Hasanatun Hasinah; Ismeth Inounu; Subandriyo Subandriyo (Chemical Engineering Diponegoro University, 2015)
Gembrong goat are mainly found in eastern part of Bali Island, especially in the village of Tumbu, Karangasem. Throughout Indonesia these goats are found no more than 50 heads. This condition puts Gembrong goat in a critical status that indicates the need of emergency and quick action. The present study was carried out to assess the characteristic of this breed and to preserve it through some proposed action plan. Information was obtained by personal observation and discussion with the leader of farmer group. Body weight (BW) and various body measurement were taken from 15 head of Gembrong goat. In general, the color of Gembrong goat body is white, or partly brown or solid brown. The average body weight is of 23.2 kg for females and 30.7 kg for males. The averages Body length of males is 60 cm, height 58.2 cm, and 14.4 cm ear length in males, and in females body length is 56.2 cm, height 55.1 cm and ear length 14.2 cm. To preserve Gembrong goat population from extinction collaborative activities is needed, namely: (1) multiplication of existing Gembrong goat population, (2) Rescuing animal genetic material and (3) up-grading female Kacang goat with Gembrong male goat as to achieve 99% Gembrong goat genetic composition.